2011
DOI: 10.4049/jimmunol.1001946
|View full text |Cite
|
Sign up to set email alerts
|

Anergic Responses Characterize a Large Fraction of Human Autoreactive Naive B Cells Expressing Low Levels of Surface IgM

Abstract: B cell anergy represents an important mechanism of peripheral immunological tolerance for mature autoreactive B cells that escape central tolerance enforced by receptor editing and clonal deletion. While well documented in mice, the extent of its participation in human B cell tolerance remains to be fully established. In this study, we characterize the functional behavior of strictly defined human naïve B cells separated on the basis of their surface IgM (sIgM) expression levels. We demonstrate that cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
132
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(143 citation statements)
references
References 50 publications
8
132
1
Order By: Relevance
“…Overall, ANA autoreactivity was most common, as it was present in up to 70% of all SLE Abs and 57 and 69% of 9G4 Abs derived from healthy and SLE naive cells, respectively. Of note, this level of 9G4 ANA autoreactivity is substantially higher than previously detected in previous studies of total naive cells with similar numbers of mAbs (∼20% for healthy naive cells and 40% for SLE naive cells) by different groups and our own laboratory (3,4,44). Therefore, these results conclusively establish the high degree of autoreactivity against SLE-related Ags of Abs using VH4-34 H chains.…”
Section: Autoreactivity Of Sle 9g4 Abssupporting
confidence: 44%
See 1 more Smart Citation
“…Overall, ANA autoreactivity was most common, as it was present in up to 70% of all SLE Abs and 57 and 69% of 9G4 Abs derived from healthy and SLE naive cells, respectively. Of note, this level of 9G4 ANA autoreactivity is substantially higher than previously detected in previous studies of total naive cells with similar numbers of mAbs (∼20% for healthy naive cells and 40% for SLE naive cells) by different groups and our own laboratory (3,4,44). Therefore, these results conclusively establish the high degree of autoreactivity against SLE-related Ags of Abs using VH4-34 H chains.…”
Section: Autoreactivity Of Sle 9g4 Abssupporting
confidence: 44%
“…Our study provides conclusive evidence for the central postulate of the 9G4 model, namely the almost universal autoreactivity of naive cells expressing VH4-34 (upwards of 70%), with predominance of anti-i BCB and ANA binding, which substantially surpasses the level of autoreactivity (20%) previously detected by our group and others in non-9G4 naive cells in HC and SLE patients (3,4,44,69). Although it is possible that a component of 9G4-associated autoreactivity may be eliminated during B cell maturation in the bone marrow, these results indicate the importance of peripheral tolerance mechanisms and are consistent with our earlier studies pointing to the GC as the main site of censoring for these cells in healthy subjects (12,13).…”
Section: Discussionmentioning
confidence: 60%
“…45 Differentiation capacity of CLL cells is varied, 21,22,[46][47][48][49][50] although it is not known whether this is related to anergy in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…14 Recent studies of potential anergic B-cell populations in healthy humans have demonstrated that these cells are also hyporesponsive to differentiation-promoting signals. 45 Differentiation capacity of CLL cells is varied, 21,22,[46][47][48][49][50] although it is not known whether this is related to anergy in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly Blimp-1 and IRF4 are As well as ITP, aspects of this phenotype have also been observed in SLE, common variable immunodeficiency, and rheumatoid arthritis. 23,32 Individually, these autoimmune diseases are rare, but a common immune phenotype may streamline the development of effective therapies targeting multiple diseases. The CD95 + population of naïve B cells in particular is identified as warranting further study as a potential biomarker for this phenotype, being both correlated with disease activity within and between individuals, and robust to commonly used B-cell modulating therapies.…”
Section: Expansion Of This Cd21mentioning
confidence: 99%